Landslide Disaster Vulnerability Analysis of the Tourism Sector in West Bandung Regency - Trisnabudi, Theodora Radella Fausta; Fadhilah, Ajeng Qonita; Permatasari, Dewi Halimah; Paramesthi, Febriyanti; Cancera, Ignatia Amelie Happy; Hanum, Lathifah; Mahdi, Naufal Asyraf; Aulia, Nayla Syifa; Sepasthika, Shahlazavier Qori; Andhika, Yoga Nur; Hizbaron, Dyah Rahmawati (Universitas Muhammadiyah Surakarta, 2024)
One of the regions in Indonesia with a relatively high risk of landslides is West Bandung Regency, West Java Province. Given its active land use and dense population, this area becomes more vulnerable to the impacts of natural disasters. The objective of this research was to identify the elements and contributing causes of landslide vulnerability, especially for West Bandung Regency's tourism sector. The robust vulnerability scenarios were generated by using Spatial Multi-Criteria Evaluation (SMCE). Four scenarios of equal vulnerability, social vulnerability (SV), physical vulnerability (PV), and environmental vulnerability (EV) are produced using the SMCE technique. According to the scenario results, three districts, Rongga, Cipatat, and Parongpong, show dynamic vulnerability, whilst the remaining districts show consistent classes. The quantity of visitors and physical infrastructure, such as access to the road, are examples of social elements that significantly impact the degree of vulnerability. The study's findings led to the creation of three vulnerability classes in West Bandung Regency: low class, with values between 1.34 and 1.78, medium class, with values between 1.79 and 2.07; and high class, with values between 2.08 and 2.36. The photo-tagged map of road access and tourist destinations in West Bandung Regency provides in-depth insight into the factors that influence the vulnerability of tourist destinations, taking into account disaster risks due to geographical conditions, infrastructure readiness, and the effectiveness of mitigation efforts in balancing tourism development and environmental resilience.